Inovação na cadeia de valor em serviços : aplicação da curva da riqueza em empresas do setor de telecomunicações - Macedo, Luís Gustavo Junqueira de (Universidade do Vale do Rio dos Sinos, 2017)
This paper deals with the theme of innovation along the value chain in the environment of telecommunications organizations. Innovation activities can occur throughout all stages of the company's activities and become a means to increase the competitiveness of organizations in the context of strong competition. The present study uses the qualitative exploratory approach to analyze data collected through interviews conducted between February and March 2017. Five professionals interviewed belong to the sales area and are distributed in the four main companies in the sector, plus a fifth that works in an organization considered incoming. Based on the study, a kind of characterization of the sector and the companies surveyed was presented, identifying practical examples of innovation activities in each organization and how they can add value to the customer. To facilitate the comparative analysis of the results, a graphic model called the Curva da Riqueza was originally created by Pantaleão, Antunes Junior e Pellegrin (2007) with the objective of associating the innovation concepts found in the OSLO manual and the value chain in the most specific form of the stages of the activities in an organizations of the transformation industry. With the use of the model, the study presented the behavior of the Curva da Riqueza for each of the companies and for the sector, regarding the stages of activities and the value of appropriation. It was observed in the analyzed cases that innovation occurs incrementally, with a main focus on brand management actions and the development of new services, mainly in the development of new technologies in the area of information technology. On the other hand, innovation activities in the development of processes and after-sales services seem to be relegated to the lowest treatment, impacting the quality perception of both the customers and the professionals themselves. The exception is the incoming company that focuses on innovation activities in process development, delivery and material logistics, and for that reason, the Curva da Riqueza of this organization has an inverted format to the original version used in product industries.
Keywords: Inovação; Cadeia de valor; Serviços; Telecomunicações; Innovation; Value chain; Services; Telecommunications; ACCNPQ::Ciências Sociais Aplicadas::Administração